Local isomorphism and multinational enterprises' human resource management practices: Extending the research agenda - Ayentimi, D.; Burgess, J.; Dayaram, Kandy (Cambridge University Press, 2018)
© Cambridge University Press and Australian and New Zealand Academy of Management 2018. Local isomorphism constitutes the regulatory, cognitive and normative profile of a host country. The regulatory institutional setting reflects the rules and legislation governing collective bargaining agreements, trade unions, local content laws and employment relationships. The cultural or cognitive dimension supports the widely held cultural and social knowledge and the normative profile acknowledges the influences of social groups and organizations on acceptable normative behaviour. Earlier literature lends support to the importance of institutional profile and its influence on the design and implementation of multinational enterprises' human resource management policies and practices. This paper seeks to advance the concept of local isomorphism and highlight the implications of local isomorphism for future research on the transfer of multinational enterprises' human resource management practices across and between subsidiaries.